COMMUNITY ENGAGEMENT IN SUPPORTING THE IMPLEMENTATION OF FINANCIAL ACCOUNTING STANDARDS FOR PRIVATE ENTITIES (SAK EP) IN THE PREPARATION OF FINANCIAL STATEMENTS BY COMPANIES IN KENDARI - Hadisantoso, Erwin; Anto, La Ode; Suriadi, La Ode; Samrin, La Ode Muhammad Arfan; Astuty, Sri; Hidayat, Fadlan; Bahar, Bahar (Yayasan Education and Social Center, 2025)
This community service program aims to enhance the understanding and capability of businesses in Kendari City in preparing financial reports in accordance with the Private Entity Financial Accounting Standards (SAK EP). The initiative was motivated by the low level of accounting literacy and the limited adoption of SAK EP among business actors, which has led to restricted access to financing, suboptimal decision-making, and potential risks of tax non-compliance. Implemented over three months by an academic team from Halu Oleo University, the program comprised three key phases: socialization, technical training, and hands-on mentoring. The results demonstrated a significant improvement in participants' awareness of the importance of accounting and their practical skills in preparing SAK EP-based financial reports. Program deliverables included training modules, standardized financial report templates, and individual action plans designed to strengthen bookkeeping practices and encourage the use of accounting software. A short-term evaluation and follow-up online mentoring were conducted to support the sustainability of the program's impact. This initiative is expected to contribute to enhanced financial transparency, improved tax compliance, and increased overall competitiveness of local businesses.